The Irish piper - Latimer, Jim, 1943- (Scribner's ; Collier Macmillan Canada ; Maxwell Macmillan International Pub. Group, 1991)
In this version of the traditional tale, the Pied Piper plays upon Irish pipes and travels from County Clare in Ireland to the village of Hamelin to rid it of its rats. An author's note discusses the Piper's music and provides examples of what he may have played.